2003
DOI: 10.1093/brain/awg059
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the neurofilament light chain gene (NEFL) cause early onset severe Charcot-Marie-Tooth disease

Abstract: Neurofilament light chain polypeptide (NEFL) is one of the most abundant cytoskeletal components of the neuron. Mutations in the NEFL gene were recently reported as a cause for autosomal dominant Charcot-Marie-Tooth type 2E (CMT2E) linked to chromosome 8p21. In order to investigate the frequency and phenotypic consequences of NEFL mutations, we screened 323 patients with CMT or related peripheral neuropathies. We detected six disease associated missense mutations and one 3-bp in-frame deletion clustered in fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
207
2
5

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 278 publications
(220 citation statements)
references
References 10 publications
6
207
2
5
Order By: Relevance
“…However the frequency is higher than the level of 31.2% in Japanese CMT1 patients (Ikegami et al, 1997). Mersiyanova et al, 2000bHuehne et al, 2003Bort et al, 1997Silander et al, 1998Jordanova et al, 2003Mostacciuolo et al, 2001 Patients with the CMT1A duplication were excluded. b Patients neither CMT1A duplication nor causative mutation in PMP22, MPZ and GJB1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However the frequency is higher than the level of 31.2% in Japanese CMT1 patients (Ikegami et al, 1997). Mersiyanova et al, 2000bHuehne et al, 2003Bort et al, 1997Silander et al, 1998Jordanova et al, 2003Mostacciuolo et al, 2001 Patients with the CMT1A duplication were excluded. b Patients neither CMT1A duplication nor causative mutation in PMP22, MPZ and GJB1.…”
Section: Discussionmentioning
confidence: 99%
“…NEFL gene encoding the neurofilament light chain plays an important role in axonal structure that includes an extensive fibrous network in the cytoplasm of the neuron. Recently, mutations in NEFL gene have been found in patients with CMT2E (Mersiyanova et al, 2000a) and early onset severe CMT phenotypes (Jordanova et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…162280) lead to complex disease phenotypes that can have either AR or AD inheritance and have normal nerve conduction velocity by electrophysiologic studies (CMT2E) or reduced nerve conduction velocity (CMT1F). 74,75 …”
Section: Axon Transport and Neuropathymentioning
confidence: 99%
“…Three mutations (Pro22Ser, Leu268Pro and del322Cys-326Asn) have been reported to be associated with giant axonal neuropathies and secondary demyelination (Fabrizi et al 2004(Fabrizi et al , 2007, whereas the other mutations (Glu89Lys and Glu397Lys) were found to be associated with onion bulb formations and loss of large myelinated fibers, but not giant axonal neuropathy (Jordanova et al 2003;Züchner et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Mutations in the NEFL gene were originally reported to be associated with CMT2E (De Jonghe et al 2001;Fabrizi et al 2004). However, because some patients had markedly reduced NCVs, it was suggested that NEFL neuropathy was also relevant with CMT1F (Jordanova et al 2003).…”
Section: Introductionmentioning
confidence: 99%